THE EFFECTS OF ANIMAL AGE AND ACETIC ACID CONCENTRATION ON PIGSKIN GELATIN CHARACTERISTICS - Sompie, M.; Triatmojo, S.; Pertiwiningrum, A.; Pranoto, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
This research was aimed to study the influence of animal age and concentration of the acetic acidsolution on physical and chemical properties of pigskin gelatin. The experiment used CompletelyRandomized Design (CRD) with two factors. The first factor was animal age consisted of 3 levels (5, 7and 9 months). The second factor was concentration of acetic acid solution consisted of 3 levels (2, 4and 6 percents). The result showed that animal age had significant effect (P<0.01) on the yields, gelstrength, viscosity, protein content and pH value but interaction of animal age and concentration ofacetic acid had no significant effect (P>0.05) on the yields, gel strength, viscosity, protein content andpH value. It was concluded that pigskin gelatin from ages of 5, 7 and 9 months and acetic acidconcentration of 2, 4 and 6% had similar characteristics to the commercial gelatin, but the optimumproduction of gelatin was combination of pigskin gelatin from 7 months and of 2% acetic acid.